2003
DOI: 10.1614/0043-1745(2003)051[0523:wualiu]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Water use and light interception under Palmer amaranth (Amaranthus palmeri) and corn competition

Abstract: A study was conducted near Garden City, KS, under irrigated conditions to determine the effect of full-season Palmer amaranth infestation on corn water use efficiency and light interception in a fully developed corn canopy. Palmer amaranth at densities of 0, 0.5, 1, 2, 4, and 8 plants m−1 was established at corn planting in 1996 and 1997 and at two locations in 1998. Soil water was monitored 240 cm deep in 30-cm increments with a neutron probe each year and at each location every 10 d. Photosynthetic photon fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 22 publications
0
63
0
Order By: Relevance
“…By coexisting with weeds for 91 days, the corn crop had its final yield reduced by 15% and 18% with and without atrazine application, respectively (Table 1 and Figure 2). These values are low if compared to the majority of studies conducted with narrow row corn crops, in which interference exceeds 70% of reduction of grain yield (Kozlowski, 2002;Massing et al, 2003;Mahmoodi and Rahimi, 2009). …”
Section: Resultsmentioning
confidence: 74%
“…By coexisting with weeds for 91 days, the corn crop had its final yield reduced by 15% and 18% with and without atrazine application, respectively (Table 1 and Figure 2). These values are low if compared to the majority of studies conducted with narrow row corn crops, in which interference exceeds 70% of reduction of grain yield (Kozlowski, 2002;Massing et al, 2003;Mahmoodi and Rahimi, 2009). …”
Section: Resultsmentioning
confidence: 74%
“…They observed that green forage yield of alfalfa (Medicago sativa) was minimum where the highest weed density was present and yield was the highest where minimum weeds were present to compete with alfalfa. Massinga et al (2004) also reported a significant decrease in maize fodder yield with increased weed density.…”
Section: Fresh Fodder Yield (Ton Ha -1 )mentioning
confidence: 95%
“…Jerry et al (2004) reported a 1.8-3.5% Sorghum bicolor yield drop by adding one weed plant per 15 row meter. Massinga et al (2004) reported that an increase in the density of Amaranthus retoflexus led to decreases of the corn grain yield and forage yield of 11-74% and 1-44%, respectively. According to Weaver (1994), economic damage threshold density is defined as a weed density in which the profit resulting from weed control equals the control cost.…”
Section: Introductionmentioning
confidence: 99%